2020
DOI: 10.1177/1759720x19886494
|View full text |Cite
|
Sign up to set email alerts
|

New insights into the treatment of myositis

Abstract: The myositis syndromes include polymyositis, dermatomyositis (DM), necrotizing myopathy, inclusion body myositis (IBM), antisynthetase syndrome and overlap syndromes with myositis. These syndromes mostly occur in middle-aged patients, while juvenile DM occurs in children and adolescents. Patients mostly show a subacute weakness and myalgia in the upper and lower limbs, the diagnosis is based upon these clinical findings in combination with muscle biopsy results and specific serum autoantibodies. In recent year… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(33 citation statements)
references
References 104 publications
0
32
0
1
Order By: Relevance
“…Given that passive transfer experiments in mice showed that the antibodies are directly pathogenic ( 7 ), removal of the antibodies with plasma exchange may also be considered to produce a transient improvement. While rare patients may experience spontaneous remissions, most patients require some immunotherapy to maintain remission, and relapses upon discontinuation are not uncommon ( 2 , 8 ).…”
Section: Discussionmentioning
confidence: 99%
“…Given that passive transfer experiments in mice showed that the antibodies are directly pathogenic ( 7 ), removal of the antibodies with plasma exchange may also be considered to produce a transient improvement. While rare patients may experience spontaneous remissions, most patients require some immunotherapy to maintain remission, and relapses upon discontinuation are not uncommon ( 2 , 8 ).…”
Section: Discussionmentioning
confidence: 99%
“…These observations, although suggestive of involvement of the classical pathway, are not NAM-specific and they do not indicate that anti-SRP or anti-HMGCR are complement-fixing antibodies because complement activation is inherently associated with muscle fibre necrosis from any cause, including muscular dystrophies 77 . Open-label studies have shown that NAM responds to IVIg or rituximab, but whether this benefit is related to complement inhibition or other immunomodulatory effects is unclear 87 89 .…”
Section: Complement In Neurological Diseasesmentioning
confidence: 99%
“…In 2017, 1 of 8 patients received rituximab and a further increase in more specific and effective therapies can be expected in future. Besides rituximab, baricitinib, triple regimens and other new treatment options bear the potential to improve the situation of patients with IIM [19]. Immunosuppressive treatment was less frequently used compared to the European registry [8].…”
Section: Discussionmentioning
confidence: 99%